A Scandinavian case of skin fragility, alopecia and cardiomyopathy caused by DSP mutations. (1st January 2014) - Vahlquist, A.; Virtanen, M.; Hellström‐Pigg, M.; Dragomir, A.; Ryberg, K.; Wilson, N. J.; Östman‐Smith, I.; Lu, L.; McGrath, J. A.; Smith, F. J. D.
Summary: Congenital skin fragility is a heterogeneous disorder with epidermolysis bullosa and various skin infections as the leading causes. However, even rare diseases must be considered in the differential diagnosis of neonatal skin blistering, including some genetic syndromes with extracutaneous involvement. One such syndrome is ectodermal dysplasia due to deficiency of desmoplakin, a desmosomal protein essential for cellular cohesion in both epithelia and cardiac tissues. Desmoplakin is encoded by the DSP gene, which is localized on chromosome 6p24. Both dominant and recessive mutations in this gene have been reported to cause skin fragility and keratinization defects. We report a child born with a fragile epidermis, alopecia, thick nails, and focal hyperkeratoses on the digits and knees. She was found to have a deficiency of desmoplakin caused by compound heterozygous DSP mutations. She has gradually developed signs of a left ventricular cardiomyopathy.